Understanding Airport Leakage at Multi Airport in West Java through Accessibility Characteristics to the Airport - Putro, Heru Purboyo Hidayat; Trinanda, Rizka Fitria; Iscahyono, Achmad Fauzan (Universitas Negeri Semarang, 2023)
Airport development must pay attention to the catchment area of the surrounding airport so that there is no overlap, which leads to airport leakage problems. Airport leakage is a phenomenon where passengers avoid local airports in their area of residence and choose airports outside their territory. The scope of study in this research is West Java Multi-airport, which consists of Kertajati Airport and Husein Sastranegara Airport, as well as Soekarno-Hatta Airport and Halim Perdanakusuma Airport as airports around West Java. The purpose of this study was to determine whether the phenomenon of airport leakage occurred at the Multi-airport of West Java Province. The study findings concluded that the addition of Kertajati Airport in West Java Province improved air connectivity in terms of flight routes but was not accompanied by an increase in the number of passengers. This phenomenon can be attributed to airport leakage, whereby passengers in West Java tend to favor Soekarno-Hatta Airport and Halim Perdana Kusuma Airport. These airports provide more flight options, offering greater time flexibility and enhanced accessibility.